A system dynamics approach to management of water resources in Qatar - Khawar Naeem (17984062) (2024)
Rapid global population growth and extensive urbanization threaten water sustainability, hindering sustainable development. This issue is particularly acute in arid regions such as the Gulf Cooperation Council (GCC), where the scarce natural water resources are overexploited. Effective water resource management (WRM) is pivotal in overcoming this challenge. This holistic study presents an innovative approach to address water sustainability at a national scale by developing a WRM decision support system (DSS) leveraging system dynamics modeling (SDM). Employing a unique scenario design framework developed in this study, the DSS simulates Qatar's water resource system behavior for 2021 to 2070 according to nine clustered policy scenarios presenting different degrees of sustainability designed accounting for changes in physical, environmental, and socioeconomic patterns. Our results reveal that the “business-as-usual” (BAU) WRM policy can balance water supply and demand for only 32 years. According to the best policy scenario, the sustainability of the water supply could be ensured for up to 50 years by increasing the water supply by 10 % and reducing consumption by 10 %. Additionally, to aid policymakers in fostering water resource sustainability, groundwater conservation strategies are proposed using the unique scenario design framework by limiting the yield to the safe abstraction level and emphasizing the significance of preserving non-renewable groundwater resources as a “backstop” resource for the country. While marking the first holistic research study in Qatar by utilizing the SDM approach to tackle national-scale WRM challenges, the established WRM DSS model is equally applicable to other GCC countries and similar arid regions. Other Information Published in: Sustainable Production and Consumption License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.spc.2024.03.024